Mineralogical, Geochemical And Nutrient Analysis Of Soils From Omalos Polje -Plateau, Western Crete - N. Lydakis ? Simantiris (Society for Mining, Metallurgy & Exploration, 2005)
Preliminary results of a mineralogical, geo-chemical and nutrient analysis of soil samples collected from Omalos polje-plateau are presented. This study is part of a project concerning the relationship of lithology and mineralogy characteristics of soils of different geological origin from the island of Crete with their chemical composition, and more specifically with their ionic nutrients content. The results presented in this work show a relatively good correlation of the mineralogy and the bulk content of the soils examined with the available nutrients in soil solution.